Enforcement of environmental pollution control laws: a Malaysian case study - Ho Nyuk Onn @ Ariffin, Mariani (Inderscience Publishers, 2019)
The increased environmental awareness in the 1970s prompted nations to enact laws that criminalise polluters. This article reviews criminal enforcement of environmental violations in Malaysia by analysing the trend in environmental crime prosecutions between 2015 to 2018. The study found that the number of prosecutions continued to fall with a marked drop, the paper points out various factors related to practical difficulties and challenges to pursue criminal enforcement against environmental offenders that might partly explain the descending prosecution trend. The cooperative enforcement strategy favoured by Malaysian regulatory agency could also play a significant role in the downward prosecution trend. In light of the risk of regulatory capture, the article suggests that the cooperative enforcement, should be complemented by prosecution against certain environmental violators to ensure deterrence. The results of the study are important to provide baseline information to stimulate intellectual discourse on the roles of criminal justice system within the existing regulatory enforcement strategy and the state of environmental problems in Malaysia.